2022
DOI: 10.1111/jonm.13795
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of core competencies associated nursing management publications

Abstract: Aims This study aimed to identify high‐impact papers on global nursing to determine and analyse the publication of articles on core competencies in nursing‐related journals and the research trends in the era of globalization. Background Bibliometrics has been shown to be an effective method for analysing publications. Through bibliometrics, nursing managers and researchers can understand the trends of high‐impact international nursing core competencies research, identify mainstream research directions and obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Many nurses in research have suggested that the ability to use information is important. The rapid advancement of information technology is gradually transforming the medical and nursing care delivery model [ 38 ]. Nurses should fully utilize information technology tools to expand their service areas to adapt to this new model of care.…”
Section: Discussionmentioning
confidence: 99%
“…Many nurses in research have suggested that the ability to use information is important. The rapid advancement of information technology is gradually transforming the medical and nursing care delivery model [ 38 ]. Nurses should fully utilize information technology tools to expand their service areas to adapt to this new model of care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, advances in patient safety and quality improvement have facilitated by the creation of specialized studies to improve recommendations in patient safety, as well as a growing number of studies on patient safety education. However, although administrators and educational researchers now have quick access to patient safety education papers, patient safety education still lacks a systematic approach and conducted in different ways, and is a need for a systematic, interdisciplinary review and synthesis to help researchers gain a comprehensive understanding of PSE in an international perspective comprehensive summaries of PSE are available to quickly identify the prevailing trends in research on the core competencies [ 21 ]. This analysis helps to explore a roadmap for the field to understand where it is and where it might headed in the future, and to inform the literature for educational and managerial decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometrics is the use of statistical methods to analyze publications, especially for scientifc contents [1,2]. It is used to justify the role of the researchers and the research team [3] and also to identify key partners [4] and the progress of a specifc research feld [5].…”
Section: Introductionmentioning
confidence: 99%
“…Factors that infuence the characteristics of nursing journal articles could further help journal articles to be quickly transformed into nursing practice and applied to nursing management. It has been reported that bibliometric analysis might help nursing management and nursing practice, and thus some studies have been performed in the feld of nursing management [2,16]. However, these studies did not analyze the important impact of online platforms on nursing management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation